2022
DOI: 10.3390/ijerph19148457
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality and Aging: A Systematic Review on Healthy Older People, Mild Cognitive Impairment and Alzheimer’s Disease

Abstract: Aging is characterized by changes in the structure and quality of sleep. When the alterations in sleep become substantial, they can generate or accelerate cognitive decline, even in the absence of overt pathology. In fact, impaired sleep represents one of the earliest symptoms of Alzheimer’s disease (AD). This systematic review aimed to analyze the studies on sleep quality in aging, also considering mild cognitive impairment (MCI) and AD. The review process was conducted according to the PRISMA statement. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 143 publications
3
36
0
Order By: Relevance
“…Second, there is an urgent need to define a standard protocol for assessing cognitive decline, specifying which tests should be used, assessing all the main cognitive domains, and clearly defining the diagnostic criteria. In addition, the need to control the extent to which cognitive decline may represent the effect of other psychological (e.g., depression and anxiety) or behavioral (e.g., sleep quality) factors may be suggested, considering the close interconnection between these factors (107) and the effects of poor sleep on cognitive decline (117).…”
Section: Discussionmentioning
confidence: 99%
“…Second, there is an urgent need to define a standard protocol for assessing cognitive decline, specifying which tests should be used, assessing all the main cognitive domains, and clearly defining the diagnostic criteria. In addition, the need to control the extent to which cognitive decline may represent the effect of other psychological (e.g., depression and anxiety) or behavioral (e.g., sleep quality) factors may be suggested, considering the close interconnection between these factors (107) and the effects of poor sleep on cognitive decline (117).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we hypothesized that the increase of neck circumference may imply changes in airway anatomy, which may be related to the severity of OSA, although no significance difference was found in BMI or AHI indices between the two groups. Characteristics of sleep disorders include decreased sleep duration and quality, reduced sleep efficiency, fragmented sleeping and sleepiness all day ( Casagrande et al, 2022 ). Previous studies have also shown that sleep disorders are associated with declined cognitive level ( Bubu et al, 2020 ), particularly impairements showed in attention, memory and executive.…”
Section: Discussionmentioning
confidence: 99%
“…4 The most commonly reported sleep disorders in AD are insomnia, sleep-disordered breathing (SDB), restless legs syndrome, and rapid eye movement (REM) sleep behavior disorder. 81 While sleep disorders may contribute to AD pathophysiology, AD-related pathology contributes to sleep problems. 81 Sleep disorders can exacerbate cognitive symptoms by impairing sleep-dependent memory consolidation processes.…”
Section: Sleep Disordersmentioning
confidence: 99%